Women's experiences of delay in labour: the holds pilot. (18th April 2012) - Armstrong, N; McNicol, S; Willars, J; Markham, C; Kenyon, S
Abstract : Background: Relatively little is known about the experiences of women who become delayed in labour, and the evidence that does exist presents a mixed picture. For example, two UK-based studies using questionnaires found that intervention for delay was not necessarily viewed as negative by women, 1 2 while two more recent small-scale interview studies from Scandinavia have shown delay can be problematic and lead women to need particular support from health professionals.3 4 Methods: We undertook individual semi-structured interviews with a diverse sample of 18 women with confirmed delay in labour. Data were analysed using the constant comparative method. Results: While all women reported feeling that they understood what was happening to them most of the time they were in labour, and felt well supported by staff, there were some periods for the majority when this had not been the case and they had struggled to keep up with what was going on. Factors that contributed to this included: pain; the effects of pain relief; tiredness; and being in an unfamiliar environment. On the whole, women were accepting of the fact that the delay they were experiencing meant that they had fewer choices available to them during labour and birth than perhaps they would have liked. Conclusions: Women generally felt well-supported but there were 'crunch points' for many when explanations by health professionals about what was happening and why were not as forthcoming or as helpful as women would have liked.